Ezquerra del Bayo y la lengua de la minería del siglo XIX - Gutiérrez Cuadrado, Juan (Revista de Investigación Lingüística, 2017)
It seems right to assert that in the XVIII and XIX centuries the Spaniards had access to the modern science through the French language. But this should be revise during the XIX century. In fact, during the XIX century, other European languages, spe- cially English and to a lesser degree German, appeared in different texts. Thus, as the cen- tury goes on, the loans from the French lan- guage not always are due to the preassure of the French culture, as in the XVIII, but to the natural acceptance of the Spaniards of loans from other Roman languages. Thus, we know the etymology of certain terms but we ignore their origin in Spanish. I would like to draw the attention to these complex relations on the works of Ezquerra del Bayo (1793 – 1859) geologist and expert in mining who left cultural and linguistic comments on his works.